Increased Threshold Voltage of Amorphous InGaZnO Thin-Film Transistors After Negative Bias Illumination Stress - Dongsheng Hong; Bing Zhang; Dongli Zhang; Mingxiang Wang; Rongxin Wang (IEEE Journal of the Electron Devices Society)
Degradation phenomena featured with positive shift of the on-state transfer curve are reported for the amorphous InGaZnO (a-IGZO) thin-film transistors (TFTs) under negative bias illumination stress (NBIS). Such a positive shift is absent when the gate bias or the illumination is independently applied. With the assistance of TCAD simulation, the positive shift of the transfer curve is attributed to the generation of acceptor-like trap states, which is proposed to be due to oxygen interstitials produced as a consequence of electron generation by the illumination, acceleration under the effect of negative gate bias, and breaking weakly bonded oxygen. The proposed degradation mechanism is consistent with the low frequency noise characteristics and the degradation behavior under bipolar gate bias stress of the TFTs after NBIS. The whole degradation phenomena for the a-IGZO TFT under the NBIS are then consistently explained.